2015
DOI: 10.1038/aps.2014.168
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype-dependent alteration of pathways and networks reveals a pure synergistic mechanism for compounds treating mouse cerebral ischemia

Abstract: Aim: Our previous studies have showed that ursodeoxycholic acid (UA) and jasminoidin (JA) effectively reduce cerebral infarct volume in mice. In this study we explored the pure synergistic mechanism of these compounds in treatment of mouse cerebral ischemia, which was defined as synergistic actions specific for phenotype variations after excluding interference from ineffective compounds. Methods: Mice with focal cerebral ischemia were treated with UA, JA or a combination JA and UA (JU). Concha margaritifera (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…for the treatment of stroke and brain ischemia/reperfusion. This study provided new insight into the combination therapy of pure synergism [16] . Dose alterations result in variations of Fangji's action.…”
mentioning
confidence: 87%
“…for the treatment of stroke and brain ischemia/reperfusion. This study provided new insight into the combination therapy of pure synergism [16] . Dose alterations result in variations of Fangji's action.…”
mentioning
confidence: 87%
“…Our prior experimental results indicated that infarction volume was significantly reduced after treatment with all compounds compared with the vehicle group except CM (P < 0.05, ANOVA). Thus, we considered the CM groups as a negative group, and the other groups as positive groups Wang et al, 2015;Li et al, 2016). According the CI calculation, we found that JU exerted a synergistic pharmacological effect and BJ had an additive effect .…”
Section: Pharmacodynamics Effects Of Reducing Ischemic Infarct Volumementioning
confidence: 99%
“…This means that the "most effective shotgun" must be identified from a series of "magic shotguns", a task that has remained challenging until now. In this paper, using a microarray containing 374 stroke-related genes and ingenuity pathway analysis (IPA) software, we compared the networks perturbed by positivephenotype ingredients (BA, JA and additive combination BJ) to those perturbed by negative-phenotype ingredients (concha margaritifera, CM) to investigate the pure pharmacological mechanism contributing to phenotype variation by eliminating non-specific roles modulating network rewiring [39] .…”
Section: Introductionmentioning
confidence: 99%